2015
DOI: 10.1097/qad.0000000000000790
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of antiretroviral therapy at high CD4+ cell counts is associated with positive treatment outcomes

Abstract: Objective There is limited research investigating the possible mechanisms of how starting combination antiretroviral therapy (cART) at a higher CD4+ cell count decreases mortality. This study investigated the association between initiating cART with short-term and long-term achievement of viral suppression; emergence of any drug resistance and of an AIDS-defining illness (ADI); long-term treatment adherence; and all-cause mortality. Methods This retrospective cohort study included 4120 naive patients who ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 50 publications
3
34
0
Order By: Relevance
“…Eighteen studies provided data on 62,823 participants that could be included in the meta-analysis, 20, 21,23,24,[27][28][29][30][31][32]35,36,40,42,44,45,48,49 among which 11 provided adjusted estimates (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies provided data on 62,823 participants that could be included in the meta-analysis, 20, 21,23,24,[27][28][29][30][31][32]35,36,40,42,44,45,48,49 among which 11 provided adjusted estimates (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…This could have contributed to the poorer adherence seen in men than women in our study. The majority of studies have reported no sex difference with respect to adherence [23][24][25][26][27][28], with one meta-analysis reporting a marginal association of male sex with higher adherence [17].…”
Section: Discussionmentioning
confidence: 99%
“…This could have contributed to the poorer adherence seen in men than women in our study. The majority of studies have reported no sex difference with respect to adherence [22][23][24][25][26][27], with one metaanalysis reporting a marginal association of male sex with higher adherence [16].…”
Section: Discussionmentioning
confidence: 99%